STATINA touch interface engine (part I) - Hendi Rusli. (2011)
Current means for human-machine interface (HMI) technology relies heavily on alphanumeric keyboard and the optical pointing device (i.e. mouse). As new interactive digital media software applications continue to evolve over the years, one of the main drawbacks of such input devices is that they restrict ease of software operation or data manipulation which require complex user input operations. This project aims to develop a new concept for human-machine interaction so as to address challenges as described above. This can be achieved by transforming everyday objects such as tabletops and glass panels into a human-machine interface using a network of low-cost surface mounted sensors. These sensors will be utilized along with signal processing algorithms such as the use of time-differences-of-arrival (TDOA) to localize and track movement of by tapping of fingers on different materials (e.g. wood, glass, plastic, etc). These locations can be used to control software applications on the PC. The outcome of this research will benefit, for example, patients with physical, sensory as well as developmental disabilities undergoing physiotherapy or requiring assistive technologies. Software applications can be developed according to patients’ requirements for motor disability rehabilitation.